The Impact of Citarum Harum Project on Ecoliteracy Among Upper Citarum Residents - Mangambit Juliandar; Dede Rohmat; Iwan Setiawan; Nandi Nandi (Geosfera Indonesia, 2023)
The Citarum River is facing pollution and damage due to domestic and industrial activities. The provincial and national governments have implemented several programs to address the Citarum issue. One key aspect of rehabilitating the Citarum River basin is the increase in environmental awareness among the community. This research aims to examine the influence of the Citarum Harum Program on the formation of Eco-literacy among the communities in Upper Citarum. A survey was conducted with 393 respondents who reside along the banks of the Upper Citarum River, distributed across the 8 sectors of the Citarum Harum Program. The research instruments used include structured questionnaires, documentary studies, and interview guidelines. Data analysis was performed using the Structural Equation Modeling (SEM) technique with SmartPLS software version 3.2.9. The results of the study indicate that Eco-literacy (ECO) has a positive correlation with the handling of existing problems (HP) with a t-value of 1.136. Eco-literacy (ECO) has a negative correlation with the physical, social, and environmental characteristics (CH) with a t-value of -0.486, as well as with the occurrence of problems with a t-value of -0.237. This suggests that the formation of eco-literacy among the communities in Upper Citarum is highly dependent on the efforts undertaken by the task force. However, there is currently no connectivity between the knowledge and attitudes of the community towards actions in the restoration of river pollution and damage.